ARTERIO-MESENTERIC COMPRESSION OF THE DUODENUM. RECURRENT POSTOPERATIVE FISTULAS OF ANTERIOR ABDOMINAL WALL (CASE REPORT) - Y. G. Grigoryev; S. A. Gelfand; N. I. Ayushinova; T. V. Ochirova; M. B. Ageyenko; V. I. Kaporskiy (Неотложная медицинская помощь, 2016)
ABSTRACT .The work presents the result of diagnostics and treatment of the patient with chronically disturbed passage of upper gastrointestinal tract, caused by chronic arterio-mesenteric compression of the duodenum and multiple recurring postoperative fistulas of anterior abdominal wall.